2001
DOI: 10.1023/a:1011182524684
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HER2, p53, bcl-2, topoisomerase II-α, heat shock proteins 27 and 70 in primary breast cancer and metastatic ipsilateral axillary lymph nodes

Abstract: 1) No biological marker had 100% concordant results. 2) Although some discordant cases might be explained by the limitations of the IHC technique, future studies aiming to evaluate the predictive value of BM in the adjuvant therapy of breast cancer should take into account a possible difference in BM expression between the primary and the metastatic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 12 publications
4
46
0
Order By: Relevance
“…31,32 It is interesting to note that, in both patients with discordant results, amplified HER-2 was detected in the primary tumors but not in the metastases. Another study also reported a loss of HER-2 overexpression in 2 of 44 metastases, 8 but several others described a converse pattern [15][16][17]42,43 or full concordance without either loss or gain of HER-2 amplification. 29,44,45 Together, these findings indicate that the HER-2 gene, although involved in initiating breast oncogenesis, does not appear to be linked directly with tumor dissemination.…”
Section: Discussionmentioning
confidence: 98%
“…31,32 It is interesting to note that, in both patients with discordant results, amplified HER-2 was detected in the primary tumors but not in the metastases. Another study also reported a loss of HER-2 overexpression in 2 of 44 metastases, 8 but several others described a converse pattern [15][16][17]42,43 or full concordance without either loss or gain of HER-2 amplification. 29,44,45 Together, these findings indicate that the HER-2 gene, although involved in initiating breast oncogenesis, does not appear to be linked directly with tumor dissemination.…”
Section: Discussionmentioning
confidence: 98%
“…Controversial opinions exist both about the stability of HER-2 status in breast carcinoma throughout the course of the disease, and about whether chemotherapy (neoadjuvant or adjuvant) can modify HER2 status. Most data have shown good overall concordance between primary and metastatic lesions, [9][10][11][12][13][14][15] but some data have demonstrated discordance in up to 20% of cases. 9,12,[16][17][18] These differences could be due to a possible genetic drift or clonal selection for HER-2, which may happen during tumour progression, 16 or to the presence of intratumoural heterogeneity of HER-2 status, [19][20][21] with a clone having enhanced metastatic potential, leading to metastases with different HER-2 status from that of the primary lesion.…”
mentioning
confidence: 99%
“…Overall HER2 tends to correlate well between primary tumors and metastatic sites but significant variations in discordance rates have been reported (2% -27%) [25]. Cardoso et al studied the correlation of HER2 in primary breast carcinoma and lymph node metastases in a large archival material (n = 370) [11]. In this study the overall percentage of discordant marker status was 2%; however, for the tumors that were lymph-node positive, 15% were negative in the primary tumor.…”
Section: Introductionmentioning
confidence: 68%
“…Assuming that the lymph node metastases represent a migrated fraction of the primary tumor cells, the metastatic cells would, conceivably, share an identical molecular profile [5]. Recent research has shown that the heterogeneity and clonal diversity seen in breast cancer contradict this notion [6]- [11].…”
Section: Introductionmentioning
confidence: 99%